The dilemma of land green use efficiency in resource-based cities: a perspective based on digital transformation - Qian, Qiulan; Luo, Shuangcheng (Frontiers in Environmental Science, 2024)
Improving land use efficiency is a necessary way to promote sustainable urban development. Existing literature mainly studies the influencing factors of land use efficiency from the aspects of economic growth and industrial structure, and there is a lack of research on how to improve the land green use efficiency(LGUE) of resource cities from the perspective of digital transformation. This paper theoretically explores the impact mechanism of digital transformation on the LGUE. Using the stochastic frontier analysis to measure LGUE in China cities, it is found that resource-based cities are 20.4% lower than non-resource-based cities. It is further found that digital transformation significantly improves LGUE, and the effect is greater in resource-based cities, which is a powerful tool to solve the difficulty of LGUE in resource-based cities. Specifically, digital transformation helps to improve the LGUE of resource-based cities enhance by technological innovation and industrial structure upgrading, and alleviating land factor mismatch. Therefore, it is not only necessary to guide and encourage the in-depth integration of traditional industries with digital technology to enhance the digital transformation of resource-based cities, but also to continuously optimize the allocation of land resources between regions and narrow the gap in LGUE between cities.